2012
DOI: 10.1093/jxb/ers066
|View full text |Cite
|
Sign up to set email alerts
|

The BnGRF2 gene (GRF2-like gene from Brassica napus) enhances seed oil production through regulating cell number and plant photosynthesis

Abstract: Seed yield and oil content are two important agricultural characteristics in oil crop breeding, and a lot of functional gene research is being concentrated on increasing these factors. In this study, by differential gene expression analyses between rapeseed lines (zy036 and 51070) which exhibit different levels of seed oil production, BnGRF2 ( Brassica napus growth-regulating factor 2-like gene) was identified in the high oil-producing line zy036. To elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 70 publications
4
103
0
1
Order By: Relevance
“…These results indicate therefore that the large size of BrGRF-OX organs is due to increases in cell numbers, but not due to increases in cell size. Our data are well in agreement with previous studies in which overexpression of AtGRFs, BnGRF2, and BrGRF8 promoted cell proliferation activities and thus increased organ size (Kim and Lee 2006;Liu et al 2012;Wang et al 2014). In conclusion, the seven BrGRFs examined in this study seem to act as positive regulators of the cell proliferation process, consequently determining the final size of organs.…”
Section: Pleiotropic Phenotypes Of Brgrf-ox Plants With Respect To Grsupporting
confidence: 93%
See 3 more Smart Citations
“…These results indicate therefore that the large size of BrGRF-OX organs is due to increases in cell numbers, but not due to increases in cell size. Our data are well in agreement with previous studies in which overexpression of AtGRFs, BnGRF2, and BrGRF8 promoted cell proliferation activities and thus increased organ size (Kim and Lee 2006;Liu et al 2012;Wang et al 2014). In conclusion, the seven BrGRFs examined in this study seem to act as positive regulators of the cell proliferation process, consequently determining the final size of organs.…”
Section: Pleiotropic Phenotypes Of Brgrf-ox Plants With Respect To Grsupporting
confidence: 93%
“…In the transgenic plant seeds, the amount of most fatty acids increased compared with the wild-type, however the composition of various fatty acids in the transgenic plant seeds are not significantly changed compared with the wild-type (Supplemental Table 5). Similarly, it has been reported that up-regulation of OsGRF4 in rice and overexpression of BnGRF2 in A. thaliana greatly enhanced the size, weight, and yield of seeds (Che et al 2016;Duan et al 2016;Hu et al 2015;Li et al 2016;Liu et al 2012). In addition, Arabidopsis seeds overexpressing BnGRF2 contained 10% more oil than wild-type seeds (Liu et al 2012).…”
Section: Pleiotropic Phenotypes Of Brgrf-ox Plants With Respect To Grmentioning
confidence: 72%
See 2 more Smart Citations
“…flowering and siliquae formation are consistent with the findings of other studies in which leaves were reported to be important sources of Pn up to flowering when stems and siliquae become more significant exporters of Pn (Uddin et al, 2012). Increase in Pn was due to increased chlorophyll content (Liu et al, 2012, Sharma et al, 2014. Further, genes associated with cell proliferation, photosynthesis and oil synthesis were unregulated which revealed photosynthesis contributed to increased seed weight and oil content.…”
Section: Introductionsupporting
confidence: 88%